An investigation into the effect of nasogastric intubation on markers of autonomic nervous function. Issue 3 (1st August 2021) - Abdul‐Razakq, Humayra; Emmanuel, Anton; Brugaletta, Concetta; Sweis, Rami; Perring, Stephen
Abstract: Background: Nasogastric (NG) intubation for esophageal manometry can be traumatic and may be associated with a temporary reduction/absence in esophageal peristalsis. This study explored the prevalence and effect on esophageal motor function. We also hypothesized that baseline anxiety as well as markers of autonomic nerve function were correlated to attenuated esophageal peristalsis. Methods: Twenty‐seven patients with esophageal symptoms referred for esophageal manometry investigation (mean age 56.8 ± 16.7 years, range 23–85 years) reported baseline anxiety score (Likert scale) preintubation. Patients had continuous heart rate and blood pressure measured prior to intubation and until 10 min after catheter withdrawal. Quality of motility was assessed for each 5 ml water swallow using standard Chicago Classification metrics. Key Results: Nasogastric‐intubation elicited a significant increase in heart rate ( p < 0.001), systolic ( p < 0.001) and diastolic ( p < 0.001) blood pressure, which was in part anticipatory. The median time taken for patients' first hypotensive peristalsis (Distal Contractile Integral; DCI ≥100 mmHg s cm) was 130 s (Interquartile range; 47–242 s) and for their first normal peristalsis (DCI ≥450 mm Hg s cm) was 150 s (IQR 61‐320 s), with improvement and consistent stabilization in DCI there onward. This corresponded closely to the time for initial recovery of heart rate and systolic and diastolic blood pressure postintubation. Conclusions and Inferences: Nasogastric intubation resulted in heightened sympathetic responses and/or dampened parasympathetic responses, and an associated temporary reduction or absence in esophageal peristalsis. Abstract : In patients who underwent nasogastric intubation, there was a confirmed temporary inhibition in esophageal peristalsis, with improvement and consistent stabilization in distal contractile integral (DCI) there onward. This corresponded closely to the time for initial recovery of heart rate and systolic and diastolic blood pressure postintubation.